Surface enhanced infrared spectroscopy using gold nanoantennas - Pucci, Annemarie; Neubrech, Frank; Weber, Daniel; Hong, S.; Toury, T.; de la Chapelle, M. Lamy (Physica status solidi. B, Basic solid state physics, 2010)
The sensitivity of infrared (IR) vibration spectroscopy can be enhanced by several orders of magnitude if plasmonic electromagnetic nearfield enhancement is exploited. For maximum enhancement the plasmonic resonance needs to be strong, which cannot be achieved by randomly grown metal island films that on average may show already signal enhancement of the order of 1000. Metal nanowires may give sufficiently strong antenna-like plasmonic resonances in the IR that can be adjusted to the molecular vibration frequencies of interest via the wire length. With individual gold nanowires we obtained vibration-signal enhancement up to 500,000 for molecular monolayers adsorbed on gold nanowires. The already obtained enhancement is not a limit. Since antennae coupled via nanogaps should enable strong electromagnetic nearfield enhancement in these gaps, respective arrays would be ideal for surface enhanced IR spectroscopy. First experiments prove the tendency of increasing vibration-signal enhancement with decreasing gap size.